Effects of p-Synephrine during Exercise: A Brief Narrative Review - Ruiz-Moreno, Carlos (Nutrients, 2021)
The p-synephrine is the principal phytochemical found in bitter orange (Citrus aurantium). This substance is widely included in dietary supplements for weight loss/body fat reduction due to its potential benefits of increasing fat oxidation. For years, p-synephrine-containing dietary supplements have been marketed without proper knowledge of their true effectiveness to enhance fat utilization, especially when combined with exercise. However, the effects of p-synephrine on fat oxidation during exercise have been investigated in the last few years. The aim of the current discussion is to summarize the evidence on the effects of p-synephrine intake on fat oxidation and performance during exercise. Previous investigations have demonstrated that the acute intake of p-synephrine does not modify running sprint performance, jumping capacity, or aerobic capacity. However, the acute intake of p-synephrine, in a dose of 2–3 mg/kg of body mass, has been effective to enhance the rate of fat oxidation during incremental and continuous exercise. This effect has been observed in a range of exercise workloads between 30% and 80% of peak oxygen uptake (VO(2peak)). The p-synephrine has the ability to increase the maximal rate of fat oxidation during exercise of increasing intensity without affecting the workload at which maximal fat oxidation is obtained (Fatmax). The effect of p-synephrine on fat oxidation is normally accompanied by a concomitant reduction of carbohydrate utilization during exercise, without modifying the energy expended during exercise. The shifting in substrate oxidation is obtained without any effect on heart rate during exercise and the prevalence of adverse effects is negligible. Thus, the acute use of p-synephrine, or p-synephrine-containing products, might offer some benefits for those individuals seeking higher fat utilization during exercise at low to moderate intensities. However, more research is still necessary to determine if the effect of p-synephrine on fat oxidation during exercise is maintained with chronic ingestion, in order to ascertain the utility of this substance in conjunction with exercise programs to produce an effective body fat/weight loss reduction.